2017
DOI: 10.1038/srep43631
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal discrimination of immune cells using a combination of Raman spectroscopy and digital holographic microscopy

Abstract: The ability to identify and characterise individual cells of the immune system under label-free conditions would be a significant advantage in biomedical and clinical studies where untouched and unmodified cells are required. We present a multi-modal system capable of simultaneously acquiring both single point Raman spectra and digital holographic images of single cells. We use this combined approach to identify and discriminate between immune cell populations CD4+ T cells, B cells and monocytes. We investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…It also requires very low light intensity, thus rendering the approach free from phototoxicity. It has been demonstrated that RS and DHM can be used simultaneously to provide a morphological and biochemical analysis of cells [ 58 ] and it can be applied to living white blood cells [ 59 ]. The phase map can provide information on the shape, dimensions and presence of cell defects that can be correlated with the biochemical information provided by single-point Raman spectra of the analyzed cells [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…It also requires very low light intensity, thus rendering the approach free from phototoxicity. It has been demonstrated that RS and DHM can be used simultaneously to provide a morphological and biochemical analysis of cells [ 58 ] and it can be applied to living white blood cells [ 59 ]. The phase map can provide information on the shape, dimensions and presence of cell defects that can be correlated with the biochemical information provided by single-point Raman spectra of the analyzed cells [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…That is true for standardized and reproducible expansion of defined immune cell preparations as well as for estimates and methods of measuring specific functionalities of an expanded immune cell population against tumor cells, infections, or inflammations. Moreover, there are also missing generally available methods and techniques for fast and precise measurement of homogeneity of a cell population, of characteristics of sub populations, and single cells [10][11][12][13]. All these aspects appear to be widely responsible for the limited progress by these very promising new therapies.…”
Section: Requirements and Existent Challenges In Producing Immune Celmentioning
confidence: 99%
“…However, the combination of this method with sophisticated software programs with in-depth analyses tools can lead to sharper, high-resolution Raman spectra enabling differentiating looks onto cells enabling subtype identification, quantification, analysis of functional status, etc. [10][11][12][13].…”
Section: Newer Techniques For Characterization and Production Of Immumentioning
confidence: 99%
“…Previous work focusing on the label-free holographic analysis of leukocytes analyzed either cells isolated by Ficoll density centrifugation or cells in culture. [7][8][9][10][11][12][13] Central laboratory applications require integrated workflows for a high-throughput analysis. The selective lysis of erythrocytes provides a rapid method for the isolation of leukocytes from whole blood and is widely used in commercial hematology analyzers and fluorescence flow cytometers.…”
Section: Introductionmentioning
confidence: 99%